Real-world comparison of pembrolizumab and nivolumab in advanced hepatocellular carcinoma - Yen-Hao Chen; Ching-Hua Tsai; Yen-Yang Chen; Chih-Chi Wang; Jing-Houng Wang; Chao-Hung Hung; Yuan-Hung Kuo (BMC Cancer, 2023)
Abstract Background Nivolumab and pembrolizumab have not been directly compared in clinical trials, and the aim of this study is to investigate the efficacy and safety of nivolumab versus pembrolizumab in patients with advanced hepatocellular carcinoma (HCC) in real-world practice. Methods We retrospectively reviewed patients with HCC who received intravenous nivolumab or pembrolizumab alone as second-line and later therapy. The objective response was determined according to the Response Evaluation Criteria in Solid Tumors criteria version 1.1. Adverse events (AEs) were graded based on the National Cancer Institute Common Terminology Criteria for Adverse Events, version 5.0. The Kaplan–Meier method was used to analyze progression-free survival (PFS) and overall survival (OS). Prognostic values were estimated using hazard ratios with 95% confidence intervals (CIs). Results In total, 120 patients were enrolled, including 95 who received nivolumab and 25 who received pembrolizumab. All patients were staged as Barcelona Clinic Liver Cancer stage C, and 29 patients were classified as Child-Pugh classification B (7). The response rate of the pembrolizumab and nivolumab groups were 8.0% and 7.4%, respectively. There was no significant difference in the median PFS between the pembrolizumab and nivolumab groups (2.7 months versus 2.9 months). The median OS in the nivolumab group was longer than that in the pembrolizumab group (10.8 months versus 8.1 months); however, the difference was not statistically significant. The effects of pembrolizumab and nivolumab on the median PFS and OS were consistent across the subgroups based on baseline characteristics. The severity of all AEs was grades 1–2 without treatment interruption or dose adjustment; there was no statistically significant difference in the incidence of treatment-related AEs between these two groups. Additionally, the percentage of patients receiving subsequent therapy was consistent between the two groups. Conclusion The efficacy and safety of pembrolizumab and nivolumab were comparable in the management of patients with pretreated HCC in real-world practice.